Peningkatan Kesadaran Kesehatan Kulit pada Remaja di Panti Asuhan Pondok Kasih Agape - Sukmawati Tansil Tan; Alexander Halin Santoso; Giovanno Sebastian Yogie; Hans Sugiarto; Alicia Sarijuwita (Lembaga Pengembangan Kinerja Dosen, 2023)
Skin disease in adolescents is a disease that can affect the quality of life in adolescents, both skin diseases caused by infection and non-infection. This activity is an education and skin health screening conducted on teenagers at the Pondok Kasih Agape Orphanage. Efforts to increase awareness of skin health in adolescents are a form of prevention of skin diseases and in an effort to reduce the incidence of various skin diseases in adolescents through skin health education and screening. Hoped that through this activity, teenagers' awareness of the importance of healthy skin can increase and those who experience disorders can receive therapy immediately, thereby stopping the course of the disease, preventing transmission, and preventing it from recurring.